Penegakan Hukum Tindak Pidana Perdagangan Orang terhadap Pekerja Migran Indonesia secara Non Prosedural - Risca Gladis Ratnasari; Ariyanti Ariyanti (MLJ Merdeka Law Journal, 2023)
The shortage of jobs, the low level of the economy of the people and the low competitiveness of Indonesian workers are serious problems that must be resolved by the Government. One attempt to solve the problem was by sending migrant workers abroad. But the policy still needs to be continuously improved and improved so that migrant workers can work well, their fundamental rights are protected, and they can enjoy their full income during their work. Besides, the safety of migrant workers has not been optimally protected. So far, the problem faced by the government is the minimum legal protection, starting with the recruitment process, when working outside, and then returning to the homeland. The objective of the study is to find out about the enforcement of the criminal offence of trafficking in persons against Indonesian Migrant Workers in a non-procedural manner as well as any obstacles encountered in the implementation of such an effort. The method of research used is empirical jurisprudence. The results of this study are the law enforcement conducted by the Indonesian Migrant Workers Protection Agency by postponing operations, company permits, written warnings, temporary suspension of part or all business activities, cancellation of the departure of potential migrant workers, and or return from abroad at their own expense. The long-term endeavour is to strictly monitor Indonesian labour services companies. The obstacles are the weakness of government surveillance, the lack of means and support facilities required by the police, and the long enough time to collect the identities of perpetrators and victims who are outside the city and even across the country to supplement the evidence.